THE Pengaruh Promosi dan Waiting List Haji terhadap Minat Menabung pada Produk Tabungan Haji Bank Syariah Indonesia (Studi Kasus pada Masyarakat di Kabupaten Kudus) - NISA ANISA NUR AWALIA; Kharis Fadlullah Hana Kharis Fadlullah Hana (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2025)
This study aims to analyze the effect of promotion and the Hajj waiting list on interest in saving on Bank Syariah Indonesia (BSI) Hajj Savings products among the people of Kudus Regency. The phenomenon of the long waiting list for Hajj has encouraged people to start financial planning early, while Islamic banks' promotional efforts also play a crucial role in attracting interest. Using a quantitative approach, this study uses primary data by distributing questionnaires via g-form to people in Kudus City. The number of samples of this study were 80 respondents and used purposive sampling method. The method used in the research is Multiple Regression Analysis using data analysis tools, namely SPSS version 25. Before data analysis, validity, reliability, and classical assumptions were tested, then the t test was carried out to determine the effect partially and the F test to determine the effect simultaneously. The results of this study indicate that promotion partially has a positive and significant effect on saving interest in choosing Hajj savings products at Bank Syariah Indonesia, while the Hajj waiting list has no positive and significant effect on saving interest in choosing Hajj savings products at BSI. Then the F test states that simultaneously promotion and the Hajj waiting list both have a significant and significant effect on savings interest in choosing Hajj savings at BSI.